Identifikasi Daerah Rawan Longsor secara Mikrozonasi di Jalan Alternatif Provinsi menggunakan Metode Simple Additive Weighting (SAW) - Darmawan Ikhlas Fadli; Arif Ismul Hadi; Zagita Allifya; Septi Anggriani; Rama Ramdani; Beni Syakban Idris; Refrizon Refrizon (Department of Physics, Sebelas Maret University, 2023)
The alternative provincial in Bengkulu Tengah Regency is located in a location bordering the Musi Fault segment that is part of the Great Sumatran Fault Zone. This condition makes cross-provincial roads in Central Bengkulu Regency vulnerable to natural disasters such as landslides. The purpose of the study was to determine areas that have the potential for landslides in earthquake-prone areas of Central Bengkulu Regency, Bengkulu Province, Indonesia. We performed the HVSR (horizontal to vertical spectral ratio) analysis and the simple additive weighting (SAW) method to achieve the study purpose. Field data acquisition using the PASI Gemini2 broadband seismometer (triaxial geophone). Next, we analyzed the tremor data recorded in the field using a wave spectrum. From the results of this study, we knew that the possibility of landslides in the survey area classified into three categories that is low, medium and high. Landslide risk should be paid more attention in areas with high potential, especially in densely populated areas. The main threat in the study area is an earthquake along the active Sumatran fault. Earthquakes in areas that are very steep and prone to landslides can increase the risk and cause landslides.